PD-L2 Expression in Breast Cancer Promotes Tumor Development and Progression - Yuling Sun; Jie Yang; Yachun Chen; Yundi Guo; Jian Xiong; Xuqin Guo; Yawen Zhang; Li Gu; Min Tong; Weipeng Wang; Jing Sun (Journal of Immunology Research)
Background. This work focused on investigating the role of programmed death ligand 2 (PD-L2) in the progression of breast cancer by utilizing breast cancer specimens and cells. Materials and Methods. The serum levels of soluble PD-L2 (sPD-L2) in breast cancer patients and healthy individuals were analyzed by means of the enzyme-linked immunosorbent assay, and the PD-L2 levels within 416 resected breast cancer specimens were assessed through immunohistochemistry. Concurrently, in vitro cell experiments and in vivo animal experiments were carried out to analyze the relationship between PD-L2 and the invasion and migration of breast cancer. Results. The concentration of sPD-L2 in breast cancer patients significantly increased compared to that in the control groups. Additionally, breast cancer patients with high concentrations of sPD-L2 had higher Ki67 values (≥30%) and tumor grades. PD-L2 was expressed in 79.09% of the cancer samples, which exhibited a positive correlation with the progesterone receptor (PR) and the human epidermal growth factor receptor 2 (HER2). Furthermore, we discovered that knockdown of PD-L2 inhibited the migratory and invasive abilities of both MCF-7 and MDA-MB231 cells. Conclusion. Our findings demonstrated that knockdown of PD-L2 suppressed tumor growth, providing novel insights into important biological functions.